The way of the progres: intentions of comunications through railroad between Paraná and Mato Grosso in passing of the XIX century to XX (Revista de História Regional, 2009)
The objective is to analyze a few projects of engineers, journalists and politicians whose intention was to connect the Paraná and Mato Grosso States in the period that corresponds to the second half of the 19th century to the first years of the 20th. It will be, specifically, analyzed a news article presented in 1903 on the newspaper O Guarapuavano of the journalist and military Luiz Cleve´s creation. In the article, the author presents a few railway projects, like for example, the ones of the engineers Francisco Tourinho, Beaurepaire Rohan, the Rebouças brothers, among others. The keynote of these projects, as the Cleve´s text, was the necessity of connecting the extreme-west of Paraná and Mato Grosso to the Atlantic Ocean, wishing to nationalize and civilize these regions, in times, considered full of barbarous and uncivilized happenings/behaviors.